A critical review and assessment for FRP-concrete bond systems with epoxy resin exposed to chloride environments. (1st December 2019) - Li, Jianglin; Xie, Jianhe; Liu, Feng; Lu, Zhongyu
Abstract: Fiber-reinforced polymer (FRP) composites have been widely used for retrofitting concrete structures. Furthermore, increasing numbers of researchers are concerned about the use of FRP as an externally bonded reinforcement in coastal areas. The short-term performance of FRP-strengthened concrete structures has been intensively investigated; however, the long-term properties of FRP-concrete bond systems in chloride environments have been relatively less frequently investigated to date. For the safe and economic use of FRP as a promising structural material, the durability of concrete structures externally strengthened with FRP needs to be properly understood. This study presents the recent progress and achievements in the performance of FRP-concrete bond systems subjected to chloride exposure. The durability of epoxy resin, FRP composites and the FRP-concrete interface in immersion exposure and wet-dry cycle exposure is focused in this review. The mechanism of typical failure modes of FRP-concrete interface is further investigated. Moreover, the lower bound limit of the tensile property retention of epoxy resin and FRP composites is analyzed and compared with the published specifications. Finally, recommendations for future research are also presented.